LATER-ADULTHOOD TRAUMA REENGAGEMENT: FINDINGS FROM DISCUSSION GROUPS WITH OLDER COMBAT VETERANS - Davison, E.H. (Innov Aging, 2017)
Later-adulthood trauma reengagement (LATR) is a phenomenon occurring among older Veterans who were exposed to stressful war-zone events in early adult years, functioned relatively successfully into adulthood, but begin to reminisce about combat-related experiences as they confront challenges of aging (e.g., retirement). LATR is conceptualized as a meaning-making process which may lead to growth or increased distress. The purpose of this study was to examine whether Veterans experiencing LATR benefited from a 10-week psychoeducational group presented from a lifespan developmental perspective. Thirteen older (Mage = 68) male combat Veterans completed discussion groups. Assessments of LATR, posttraumatic stress, positive appraisals of military experience, life satisfaction, resilience, and meaning-making were collected at baseline, post-group, and follow-up. Descriptive statistics revealed variability in individual responses on measures of distress, but that positive perceptions (e.g., positive appraisals) tended to increase. Additionally, the intervention was well-received: retention was high and qualitative responses indicated high satisfaction.